2012
DOI: 10.1517/14740338.2012.653560
|View full text |Cite
|
Sign up to set email alerts
|

Statin use and the risk of gallstone disease: a population-based case–control study

Abstract: This study does not provide support for a beneficial association between usage of statin and gallstone disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…The relationship between current statin used and the risk of gallstone disease were explored in the six studies. Of the six studies, two had no statistically significant difference. Pooled analyses of OR in the random‐effects model showed that subjects who used statin had a lower overall risk of gallstone disease compared with non‐users, and there was heterogeneity among the studies (OR, 0.86; 95% CI, 0.77–0.97, P = 0.018; for heterogeneity, P < 0.001, I 2 = 81.1%; Fig.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The relationship between current statin used and the risk of gallstone disease were explored in the six studies. Of the six studies, two had no statistically significant difference. Pooled analyses of OR in the random‐effects model showed that subjects who used statin had a lower overall risk of gallstone disease compared with non‐users, and there was heterogeneity among the studies (OR, 0.86; 95% CI, 0.77–0.97, P = 0.018; for heterogeneity, P < 0.001, I 2 = 81.1%; Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Occupying a portion of the binding site of HMG reductase, statins block access of this substrate to the active site on the enzyme leading to a reduction of intrahepatic cholesterol production and alterations of bile cholesterol saturation . Another possible mechanism of the action of statins on gallstone disease is inhibition of cholesterol crystal nucleation . Until 2000, large‐sample clinical observational studies on statin use and risk of gallstone disease were conducted, but no meta analysis was performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In accordance with this finding, the need of surgery of any type or the cholelithiasis outcomes did not differ between the statin and non-statin groups, which contrasted with some previous studies. In a Taiwanese study, the investigators did not find a beneficial association between statin use and gallstone disease [21]. However, in East Asia, there is a lower prevalence of gallstones, and the stones primarily have a brown pigment, which indicates that they are comprised mainly of calcium [1].…”
Section: Discussionmentioning
confidence: 99%